2020
DOI: 10.1080/2090598x.2020.1750864
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell applications in regenerative medicine for stress urinary incontinence: A review of effectiveness based on clinical trials

Abstract: Objective To evaluate the current state, therapeutic benefit and safety of urethral injection of autologous stem cells for the treatment stress urinary incontinence (SUI). Materials and methods A selective database search of PubMed, the Excerpta Medica dataBASE (EMBASE), Cochrane Library and Google Scholar was conducted to validate the effectiveness of stem cell-based therapy. The search included clinical trials published up until 4 January 2020, written in English, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Cell therapy of SUI is not yet a standard procedure despite many successfully completed preclinical animal studies reporting promising results 9 , 37 . Initially, only a few clinically feasible studies reported success 4 , the quality and type of cells injected varied considerably 37 , large cohort studies with the corresponding control groups were mostly missing 38 , follow-up in many studies remained rather short, and outcome was variable and not evaluated consistently. Drop-out during clinical feasibility trials seemed not to be worth reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Cell therapy of SUI is not yet a standard procedure despite many successfully completed preclinical animal studies reporting promising results 9 , 37 . Initially, only a few clinically feasible studies reported success 4 , the quality and type of cells injected varied considerably 37 , large cohort studies with the corresponding control groups were mostly missing 38 , follow-up in many studies remained rather short, and outcome was variable and not evaluated consistently. Drop-out during clinical feasibility trials seemed not to be worth reporting.…”
Section: Discussionmentioning
confidence: 99%
“…17 With the potential for self-renewal, durable proliferation, and differentiation, transplantation of these cells and their myoblast progeny has been investigated for therapeutic purposes to augment weakened muscle tissue and improve function. [7][8][9][10]18 Several studies have reported the formation of new muscle fibers following the injection of muscle-derived progenitor cells in a rodent hemiglossectomy model. [11][12][13] Kim et al injected a hydrogel-myoblast composite in a rat hemiglossectomy model and observed significant increase in tongue weight, evidence of neovascularization, and possible neurotization.…”
Section: Discussionmentioning
confidence: 99%
“…AMDC therapy involves the isolation and expansion of progenitor cells from skeletal muscle biopsies and their injection into the target muscle to induce fusion of the cells with existing myofibers and formation of new fibers to improve muscular function. Musclederived progenitor cells have recently shown benefit in treatment of stress urinary incontinence, 7,8 fecal incontinence 9 and myocardial infarction. 10 In animal studies, muscle-derived cells have successfully integrated within tissue to improve tongue strength and function.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-established that stem cell therapy represents a new and prospective frontier in treatment of various diseases (22). For example, Jiang et al (23) have presented that combination with chemokine (c-c motif) receptor 1 (CCR1)-overexpressing MSCs and chemokine (c-c motif) ligand 7 (CCL7) promote the SUI recovery simulated by birth injury in rats.…”
Section: Discussionmentioning
confidence: 99%